Serum Hsa_circ_0005962 Is A Prognostic Biomarker of Paclitaxel Resistance in Nonsmall Cell Lung Cancer Treatment - Chenliang Wang; Shaofeng Xia (International Journal of Clinical Practice)
Background. Tumor progression and the therapeutic resistance associated with cancer agents are thought to be modulated by circular RNAs (circRNAs); however, its mechanism associated with nonsmall cell lung cancer (NSCLC) is still undetermined. The following investigation aimed to evaluate the involvement of circRNAs with NSCLC. Methods. The serum specimens of 146 NSCLC individuals who received complete four cycles of PTX chemotherapy were collected. The serum concentration of hsa_circ_0005962 of these individuals was assessed with quantitative real-time polymerase chain reaction (qRT-PCR), followed by the evaluation of demographic and survival consequences for further assessments. Results. It was revealed that hsa_circ_0005962 is substantially increased in NSCLC chemoresistant patients and was positively correlated with the disease stage. Furthermore, the hsa_circ_0005962 value of the area under the curve was moderate, and increased hsa_circ_0005962 expression was linked with shorter overall survival (OS). Hsa_circ_0005962 stimulated paclitaxel resistance (PTX-R) in resistant NSCLC cells by regulating the axis of miR-126-5p/insulin-like growth factor 1 (IGF1). Conclusion. The results of this investigation highlight that hsa_circ_0005962 induces chemoresistance in NSCLC patients and, therefore, can act as a physiological target to treat NSCLC.